1988
DOI: 10.1002/1097-0142(19880115)61:2<298::aid-cncr2820610219>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Tumor markers in pleural effusion diagnosis

Abstract: In order to discriminate between malignant and benign effusions, the values of carcinoembryonic antigen (CEA), ferritin, beta2-microglobulin (BMG), acid-soluble glycoprotein (ASP), tissue polypeptide anti-gen (TPA), adenosine deaminase (ADA), and immunosuppressive acidic protein (IAP) were measured in the pleural fluid of 54 patients with lung cancer, 20 with malignancies other than lung cancer, 18 with tuberculous pleurisy, and 22 with benign diseases other than tuberculosis. CEA levels in malignant effusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 18 publications
1
26
0
3
Order By: Relevance
“…The results of the present study again confirm CEA as the most dependable tumour marker in pleural fluid [9,10,13], where its sensitivity was 57%, a value close to that of cytology in most series, and its specificity was 99%. The CA 15-3, with an accuracy only 4% lower than that of CEA, showed a sensitivity of 48% with a specificity of 97%, making this marker useful, either alone or in combination with other diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study again confirm CEA as the most dependable tumour marker in pleural fluid [9,10,13], where its sensitivity was 57%, a value close to that of cytology in most series, and its specificity was 99%. The CA 15-3, with an accuracy only 4% lower than that of CEA, showed a sensitivity of 48% with a specificity of 97%, making this marker useful, either alone or in combination with other diagnostic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have tried to find biochemical markers in pleural fluid which could be of value in the differential diagnosis of pleural effusions [6][7][8][9][10][11][12]. The role, if any, of tumour marker assays in differentiating malignant from benign pleural effusions is not yet clear.…”
mentioning
confidence: 99%
“…2- 15 We noted elevated levels of sialyl SSEA-1 in pleural fluid of patients with adenocarcinoma of the lung. The positive rate was 64% in adenocarcinoma, whereas it was 7.7% in nonadenocarcinoma and 0% in benign pulmonary disease when the cutoff level was defined as 300 unit/ml.…”
Section: Discussionmentioning
confidence: 63%
“…CEA has been utilized most widely as a tumor marker for serous effusions (Nystrom et al 1977 ; Whiteside and Dekker 1979 ; Vladutiu et al 1979Vladutiu et al , 1981Niwa et al 1985 ;Tamura et al 1988). In the present study, we demonstrated that the SLEX antigen could be the most useful tumor marker among the three carbohydrate antigens tested in patients with various types of cancer, and especially in pulmonary adenocarcinoma.…”
Section: Discussioi~mentioning
confidence: 74%